Attitude of General Dental Practitioners and Specialists Toward Infection Control Measures in Prosthodontics Clinics in Tripoli, Libya - Nourelhouda Misurati; Noora Berhaim; Hala Traina (Khalij-Libya Journal of Dental and Medical Research, 2022)
Background and objectives. Prosthodontics clinics require a high degree of concern regarding cross-infection of patients, personnel, unsterilized instruments, and equipment. Prosthodontics treatment undertaken in the clinics should be supplemented by the laboratory, and hence cross-infection chances have to be halted on both the fronts. The aim of this study was to evaluate attitudes regarding infection control procedures in prosthodontics clinics among general dentists, and specialists in Tripoli, Libya. Methods. A questionnaire of 11 questions was created and randomly distributed to 150 general dentists and specialists working in Tripoli’s private clinics and public health centers. The questionnaire was anonymous and consisted of questions related to vaccination status, attitude and awareness towards infection control in prosthodontics clinics. Out of which (123) questionnaires were filled, giving a response rate of 82%. The data were sorted, checked, tabulated, and statistically analyzed. Results. A total of 123 dentists (68.3%) were general practitioners and (31.7%) were specialists, (39.9%) were males, and (60.1%) were females. In this study there was a positive correlation between vaccination status and the qualification (P =0.044). As (89.7%) of the specialists stated that they had been vaccinated against Hepatitis B virus, while only (73.8%) of general dentists had been vaccinated. The study also showed statistical significance when qualification was cross‑tabulated against the responses for various questions, that is, disinfection of rubber bowl (P = 0.027), sterilization of dental cast (P = 0.032), sterilization of metal framework (P =0.009), bite registration and bite block sterilization before sending to the dental laboratory (P =0.005), custom trays sterilization (P =0.005), and sterilization of the handpiece between cases (P = 0.000). The study also revealed that while just 11.9% of general dentists disinfect the impression prior to sending it to the dental laboratory, 23.1% of specialists do so after rinsing the impression. Conclusion. The findings of this study suggest that there are insufficient attitudes toward infection control procedures in prosthodontics practice. Furthermore, the implementation of selective standard precautions, such as hand hygiene compliance, was widely practiced by the Tripoli dentists surveyed. Citation: Misurati N, Berhaim N, Traina H. Attitude of General Dental Practitioners and Specialists Toward Infection Control Measures in Prosthodontics Clinics in Tripoli, Libya. Khalij-Libya J Dent Med Res. 2022;6(2):117–124. https://doi.org/10.47705/kjdmr.226205